2014
DOI: 10.1108/bfj-08-2013-0210
|View full text |Cite
|
Sign up to set email alerts
|

Thailand's food retail transition: supermarket and fresh market effects on diet quality and health

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 29 publications
(29 reference statements)
4
52
1
Order By: Relevance
“…Modernisation of food retail outlets or ‘supermarketisation’ has been considered as an important driver of the nutrition transition that is taking place in some Asian emerging economies (Kelly et al . ; Reardon et al . ; Umberger et al .…”
Section: Introductionmentioning
confidence: 99%
“…Modernisation of food retail outlets or ‘supermarketisation’ has been considered as an important driver of the nutrition transition that is taking place in some Asian emerging economies (Kelly et al . ; Reardon et al . ; Umberger et al .…”
Section: Introductionmentioning
confidence: 99%
“…As an unintended consequence, an increasing number of consumers started shopping at uncontrolled and unhygienic street markets (Wertheim-Heck et al, 2014b). Moreover, recent studies in Thailand indicate that a decrease in wet markets, which provide affordable healthy foods, puts healthy diets at risk (Banwell et al, 2013;Kelly et al, 2014). Therefore, food safety policies that exclusively promote the supermarket retail format may actually be counterproductive.…”
mentioning
confidence: 96%
“…Supermarkets and hypermarkets until recently have been mainly located on the outskirts of towns, and therefore accessible and convenient to those who own cars, which is an increasing segment of the Thai population. Results from the 2012 survey, described earlier, have shown that over a 10 year period the proportion of the sample who had access to a supermarket increased from 47% to 85% (Kelly et al 2014). Urban residents, those who owned a bicycle or motorcycle and those who received lower incomes were more likely than others to purchase fresh produce mainly at fresh markets.…”
Section: Resultsmentioning
confidence: 96%
“…The 2012 Thai Cohort Sub‐Study demonstrated that those who mainly used modern retail formats, such as supermarkets and convenience stores, had a higher consumption of unhealthy foods such as soft drinks, snack foods, processed meats, western style bakery goods, instant foods, and deep fried foods. Those who shopped mainly at fresh markets had a higher consumption of vegetables (Kelly et al 2014).…”
Section: Resultsmentioning
confidence: 99%